Mining and quarrying activities tend to favor stress-tolerant plants. (August 2021) - Fazlioglu, Fatih; Keskin, Gulaycan P.; Akcin, Oznur E.; Ozbucak, Tugba
Highlights: Effects of anthropogenic activities on plants can be detected by CSR strategies. "StrateFy" tool can quickly track environmental changes using plant traits. Mining activities may favor stress-tolerant species. Abiotic stress may decrease functional diversity of plant communities. Abstract: Anthropogenic activities such as mining and agricultural practices may alter plant community structure and functioning. Grime's Competitors–Stress–Ruderal (CSR) strategy can be used to detect plant community transformations caused by environmental changes. We examined the effects of mining and quarrying activities on CSR strategies, species diversity, functional composition (community-weighted mean – CWM), and functional diversity (Rao's and Mason's indexes) of plant species from nearby an active Cu-Pb-Zn mine site and an agricultural site away from the mine. We determined the ecological strategies of 34 species using 13 functional traits. We found that ruderal strategy (e.g., high R-scores) was dominant in the agricultural site, whereas stress-tolerant species (e.g., high S-scores) were abundant in the mine site according to "StrateFy" that is a globally calibrated CSR analysis tool. Community-weighted mean (CWM) trait values were greater in the agricultural site where has relatively higher soil fertility than in the stressful mine site (e.g., low pH and heavy metal stress). Although species diversity was higher in the mine site, functional diversity in the agricultural site was slightly higher than that in the mine site as indicated by greater Rao's and Mason's index values. Our findings suggest that the effect of anthropogenic activities might be detected using CSR strategies both at species and community levels. Mining activities may favor stress-tolerant species, whereas agricultural practices (e.g., fertilization and mowing disturbance) may favor ruderal species in accordance with the CSR theory predictions. "StrateFy" CSR analysis tool can help us to quickly track shifts in ecological strategies of plants in response to changes in the environment and land-use. Therefore, CSR strategies can be used as bioindicators of anthropogenic activities. Moreover, under increasing abiotic stress, functional diversity of plant communities may decrease which can have crucial effects on community-level responses and eventually ecosystem functioning and services.